ผลทางเภสัชวิทยาของสารจินเซ็นโนไซด์ในโสมอเมริกาต่อสุขภาพ Pharmacological Effects of Ginsenosides from American Ginseng toward Health - วงศ์ใหญ่ รศ.ดร.สุรพจน์ (Journal of The Royal Thai Army Nurses, 2012)
บทคัดย่อ สมุนไพรโสมมีประวัติการใช้ทางการแพทย์เพื่อจุดประสงค์ในการบำรุงสุขภาพมาอย่างยาวนานมากกว่า 2,000 ปี ในโสมประกอบด้วยสารธรรมชาติที่มีฤทธิ์ทางเภสัชวิทยาชื่อว่า จินเซ็นโนไซด์ (Ginsenoside) ซึ่งในปัจจุบันมีการตรวจแยกวิเคราะห์ด้วยกระบวนการทางวิทยาศาสตร์ออกมาได้แล้วกว่า 150 ชนิด โสมอเมริกา (Panax quinquifolium) เป็นโสมมีต้นกำเนิดจากทวีปอเมริกาเหนือ และจากรายงานการศึกษาบางฉบับพบว่าสภาพแวดล้อมที่เหมาะสมในการเพาะปลูกส่งผลต่อปริมาณจินเซ็นโนไซด์ที่พบได้ในรากอย่างมีนัยสำคัญอีกด้วย และเนื่องด้วยสารสกัดจินเซ็นโนไซด์มีโครงสร้างที่หลากหลายจึงส่งผลให้นักวิทยาศาสตร์ให้ความสนใจทำการศึกษาค้าคว้าถึงฤทธิ์ทางเภสัชวิทยาที่มีความแตกต่างเหล่านี้เพื่อการนำมาพัฒนาให้เกิดความก้าวหน้าทางการแพทย์และวิทยาศาสตร์ต่อไปในอนาคต ซึ่งบทความฉบับนี้มีจุดประสงค์เพื่อรวบรวมและสรุปผลข้อมูลของโสมอเมริกาตลอดจนฤทธิ์ทางเภสัชวิทยาของจินเซ็นโนไซด์ที่มีผลต่อร่างกายในด้านต่างๆ เช่น ผลต่อระบบสมองและระบบประสาทส่วนกลาง เป็นต้น คำสำคัญ : โสมอเมริกา; จินเซ็นโนไซด์ Abstract Ginseng is the herb which has been used in Traditional Chinese Medicine (TCM) more than 2,000 years. American ginseng (Panax quinquifolium) is the plant which in the family of ginseng herb. This kind of ginseng was originated found in North America areas. According to scientific exploration, there are the major ingredients of from ginseng, namely “ginsenosides” that provide many health benefits. This kind of natural compound, recently, is categorized more than 150 types. However, from some studies indicated that the appropriate environment seems to have an impact on the ingredient content and proportion significantly. With the variation of these ginsenosides, the current scientist interested to investigate more about this compound in term of pharmacological activities which may lead to the progression and development of future scientific and medical knowledge. Thus, this review is aimed to summarize and conclude the evidence-based data of ginsenosides’ benefits to human body system such as Central Nervous System (CNS) and etc. Keywords: American Ginseng; Ginsenosides